Management of lung disease in alpha-1 antitrypsin deficiency: what we do and what we do not know - Igor Barjaktarevic; Michael Campos (SAGE Publishing, 2021)
Management of lung disease in patients with alpha-1 antitrypsin deficiency (AATD) includes both non-pharmacological and pharmacological approaches. Lifestyle changes with avoidance of environmental pollutants, including tobacco smoke, improving exercise levels and nutritional status, all encompassed under a disease management program, are crucial pillars of AATD management. Non-pharmacological therapies follow conventional treatment guidelines for chronic obstructive pulmonary disease. Specific pharmacological treatment consists of administering exogenous alpha-1 antitrypsin (AAT) protein intravenously (augmentation therapy). This intervention raises AAT levels in serum and lung epithelial lining fluid, increases anti-elastase capacity, and decreases several inflammatory mediators in the lung. Radiologically, augmentation therapy reduces lung density loss over time, thus delaying disease progression. The effect of augmentation therapy on other lung-related outcomes, such as exacerbation frequency/length, quality of life, lung function decline, and mortality, are less clear and questions regarding dose optimization or route of administration are still debatable. This review discusses the rationale and available evidence for these interventions in AATD.